Hybrid harmony search algorithm & fuzzy logic for solving unit commitment problem with wind power uncertainty - P. Varghese, Mary; Amudha, A. (International Journal of Engineering and Technology, 2018)
This work spotlights on fuzzy logic and hybrid harmony search algorithm based framework for solving the unit commitment problem in any electric utility. Here, the selection of fuzzy logic is because of its qualitative representation ability with respect to input attributes, cost-effective operating agenda and all the calculations of feasible schedules. A three-unit system is assumed here, to compute the above-mentioned aspects. In recent days, the meta-heuristic optimization algorithms are constructed because of its zero utilization and storage for making the search procedureas effective. Hybrid harmony search algorithm searches whether the load demand is met or not. If it is not satisfied an error is developed. The error and change in error is fed input to fuzzy logic unit. The output of fuzzy logic unit is given to a breaker. The breaker will cut off the system is the power output is more and if the power output is less than the required value additional power is fed to the system. Constant ouput power is thus maintained. To test and prove that the proposed HHS-FLresults a superior optimization, performance by analyzing the wind speed in Coimbatore region. The experimental results demonstrated that the proposed model is efficient even if the windgets changed and all simulations was performed with MATLAB.